The Impact of You Tube Video Creation and AI Assisted on Students’ Speaking Performance - Nurjana; Iis Sujarwati (Universitas Bengkulu, 2025)
This study investigated how students' speaking performance was affected by creating YouTube video projects using AI-assisted tools like CapCut, Canva, AI voice tools, Kine Master, Grammarly, ELSA Speak, etc. This study was quantitative in design. This pre-experimental study employed a one-group pretest-posttest strategy to ascertain whether the students' speaking performance was impacted by producing a video project. The population was eleven students in the electrical engineering program at SMKN 1 Rejang Lebong. The sample consists of 47 students. Tests, both pre- and post-test, were used to gather the quantitative data. The data were statistically analyzed using a paired sample t-test with IBM SPSS 25 for Windows. The results of this research showed that using AI to help students create a YouTube project significantly improved their speaking skills. It was an effective way to teach speaking because it improves students' speaking performance, fosters teamwork, sharpens their problem-solving abilities, and motivates them to be proactive, communicative, imaginative, and creative. As a result, using it to teach speaking is strongly advised. Keywords: AI-Assisted; Video Project; Speaking Performance